2020
DOI: 10.1002/fsn3.1434
|View full text |Cite
|
Sign up to set email alerts
|

Application of antagonist Bacillus amyloliquefaciens NCPSJ7 against Botrytis cinerea in postharvest Red Globe grapes

Abstract: We investigated the effects and possible mechanisms of Bacillus amyloliquefaciens NCPSJ7 against the gray mold caused by Botrytis cinerea in the postharvest Red Globe grapes. The disease incidence, lesion diameter, decay index, and some resistance‐related enzymes were evaluated. The antioxidant capacity of grape treated with 1 × 104 CFU/ml B. cinerea alone and combined with 1 × 107 CFU/ml NCPSJ7 was also determined. The results showed that NCPSJ7 + B. cinerea reduced the disease incidence, lesion diameter, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…In previous studies, strains belonging to Bacillus sp., the close relative of Paenibacillus , have been reported to control B. cinerea on grapes under vineyard and storage conditions, by secreting inhibitory compounds and triggering induced systemic resistance [ 29 , 30 ]. Similarly, it has been shown that Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, strains belonging to Bacillus sp., the close relative of Paenibacillus , have been reported to control B. cinerea on grapes under vineyard and storage conditions, by secreting inhibitory compounds and triggering induced systemic resistance [ 29 , 30 ]. Similarly, it has been shown that Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus amyloliquefaciens has considerable potential for biological control of plant diseases (Chen et al 2014;Xiong et al 2015;Li et al 2017). This effect is the result of multiple mechanisms, including antagonism, competition, growth promotion and induction resistance (De Silva et al 2019;Guo et al 2019;Zhou et al 2020). Generally, the antagonistic activity of antimicrobial substances is the most direct and effective mechanism to inhibit the infection and growth of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…2019; Zhou et al . 2020). Generally, the antagonistic activity of antimicrobial substances is the most direct and effective mechanism to inhibit the infection and growth of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of B. cinerea, the significant reduction in fungal growth achieved in this study is really positive due to the fact that this genus is the main fungal grape pathogen. 43 Some studies also presented a similar reduction of fungal growth by using a coating of LAB as a biopreservative on lightly damaged grapes; 44 or, like Zhou et al, 45 where the direct application of a strain of Bacillus amyloliquefaciens at concentrations of 10 7 CFU mL −1 per gram of fruit was able to reduce the growth of this fungus. In general, due to differences in the application of the treatments, no true comparisons can be performed between the methods found in the literature and this assay.…”
Section: Identification Of Antifungal Compoundsmentioning
confidence: 94%